2022
DOI: 10.1038/s41388-022-02377-9
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of mucosal microbiota reveals universal microbial signatures and dysbiosis in gastric carcinogenesis

Abstract: The consistency of the associations between gastric mucosal microbiome and gastric cancer across studies remained unexamined. We aimed to identify universal microbial signatures in gastric carcinogenesis through a meta-analysis of gastric microbiome from multiple studies. Compositional and ecological profiles of gastric microbes across stages of gastric carcinogenesis were significantly altered. Meta-analysis revealed that opportunistic pathobionts Fusobacterium, Parvimonas, Veillonella, Prevotella and Peptost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 46 publications
3
51
2
Order By: Relevance
“…Furthermore, based on the current findings, a panel of differential gastric bacteria can be developed to distinguish GC and the progression of GC with outstanding performance. A recently published meta-analysis, which enrolled six independent studies, reported that eight bacterial taxa could serve as a panel of biomarkers to discriminate GC from superficial gastritis with an area under the curve (AUC) of 0.850 (Liu et al, 2022). Regarding the progression of GC, Kadeerhan et al reported a combination of four genera (Bacillus, Capnocytophaga, Helicobater, Prevotella) with age and sex to distinguish subjects after lesion progression from non-progression controls (AUC = 0.927) (Kadeerhan et al, 2021).…”
Section: The Non-h Pylori Microbes Associated With Gcmentioning
confidence: 99%
“…Furthermore, based on the current findings, a panel of differential gastric bacteria can be developed to distinguish GC and the progression of GC with outstanding performance. A recently published meta-analysis, which enrolled six independent studies, reported that eight bacterial taxa could serve as a panel of biomarkers to discriminate GC from superficial gastritis with an area under the curve (AUC) of 0.850 (Liu et al, 2022). Regarding the progression of GC, Kadeerhan et al reported a combination of four genera (Bacillus, Capnocytophaga, Helicobater, Prevotella) with age and sex to distinguish subjects after lesion progression from non-progression controls (AUC = 0.927) (Kadeerhan et al, 2021).…”
Section: The Non-h Pylori Microbes Associated With Gcmentioning
confidence: 99%
“…The predominant role of H. pylori in GC development has triggered an increasing interest in the study of gastric dysbiosis in last decade (17). In fact, gastric microbiota composition is highly variable between individuals (18).…”
Section: Gastric Dysbiosis As a Main Player In Early Gastric Carcinog...mentioning
confidence: 99%
“…, Veillonella and Parvimonas ) was observed concomitantly with a decrease in putative probiotics ( e.g. , Bifidobacterium ) throughout the stages of disease progression[ 41 ]. Another study has suggested that successful eradication of H. pylori could reverse the tendency towards gastric microbiota dysbiosis and show beneficial effects on the gastric microbiota[ 42 ].…”
Section: Pathogenesis Of H Pylori Gastric Infectionmentioning
confidence: 99%